2017
DOI: 10.1371/journal.pone.0171258
|View full text |Cite
|
Sign up to set email alerts
|

3D-modeling of the spine using EOS imaging system: Inter-reader reproducibility and reliability

Abstract: ObjectivesTo retrospectively assess the interreader reproducibility and reliability of EOS 3D full spine reconstructions in patients with adolescent idiopathic scoliosis (AIS).Methods73 patients with mean age of 17 years and a moderate AIS (median Cobb Angle 18.2°) obtained low-dose standing biplanar radiographs with EOS. Two independent readers performed “full spine” 3D reconstructions of the spine with the “full-spine” method adjusting the bone contour of every thoracic and lumbar vertebra (Th1-L5). Interrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…The MDSS imaging system takes simultaneous images in two planes (posterior-anterior and lateral). By using a computer algorithm, the system can construct three-dimensional (3D) surface images from the simultaneous two-plane images 5,6 . The MDSS is designed to lower patient doses compared with conventional digital radiography (DR) X-ray imaging systems and a few studies have shown substantial clinical potential for dose savings compared to DR and computed radiography (CR) [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The MDSS imaging system takes simultaneous images in two planes (posterior-anterior and lateral). By using a computer algorithm, the system can construct three-dimensional (3D) surface images from the simultaneous two-plane images 5,6 . The MDSS is designed to lower patient doses compared with conventional digital radiography (DR) X-ray imaging systems and a few studies have shown substantial clinical potential for dose savings compared to DR and computed radiography (CR) [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…EOS is commercialized by the French company EOS imaging for orthopaedic applications. Nowadays in many developed countries EOS imaging system is applied in several hospitals and many researchers have used this system for 3D reconstruction of diverse bone structures such as Mitton et al (2006) for Pelvis, Baudoin et al (2008), Chaibi et al (2011), andQuijano et al (2013) for Lower Limb, Lebailly et al (2012) for Upper Limb, Aubert et al (2014) for Rib cage, Humbert et al (2009) and Rehm et al (2017) for Spine. However, this system is still unavailable in many developing countries and medical centres because of some restrictions such as costs.…”
Section: Perspective Model Based Methodsmentioning
confidence: 99%
“…16 Full spine 3D reconstructions were made using sterEOS software V1.4.4.5297, which is aligned by the user to the contours of each thoracic and lumbar vertebra. 17 The software automatically calculates the Cobb angle, curvature level in addition to the serial AVR values for Th1-L5 vertebrae ( Figure 1). AVR was calculated based on the axial displacement of the vertebrae relative to the pelvis, with left hand rotation defined as positive.…”
Section: Imaging Protocol and 3d Modelingmentioning
confidence: 99%